1990
DOI: 10.1002/bms.1200190308
|View full text |Cite
|
Sign up to set email alerts
|

The use of electron impact and positive chemical ionization mass spectrometry in the screening of beta blockers and their metabolites in human urine

Abstract: The use of several mass spectrometry technologies including electron impact (EI) and positive chemical ionization (CI) in both full-scan and multiple ion detection (MID) analysis for the urine analysis of several beta blockers and metabolites has been investigated. These drugs were extracted using an alkaline solid-phase extraction procedure and identified as their respective trimethylsilyl-trifluoroacetyl (TMS-TFA) derivatives on capillary gas chromatography/mass spectrometry. Isobutane proved to be the prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…5 ) by capilliary gas chromatography/mass spectrometry after solid-phase extraction and a trimethylsilylationtrifluoroacetylation derivatization reaction. Details ot this procedure have been published elsewhere (Leloux and Maes, 1990b). Our results have revealed that these three metabolites were formed irrespective of the stereochemical constitution of the beta-blocking drug infused.…”
Section: Pharmacokinetic/pharmacodynamic (Pk/pd) Modelling Of Metopromentioning
confidence: 61%
“…5 ) by capilliary gas chromatography/mass spectrometry after solid-phase extraction and a trimethylsilylationtrifluoroacetylation derivatization reaction. Details ot this procedure have been published elsewhere (Leloux and Maes, 1990b). Our results have revealed that these three metabolites were formed irrespective of the stereochemical constitution of the beta-blocking drug infused.…”
Section: Pharmacokinetic/pharmacodynamic (Pk/pd) Modelling Of Metopromentioning
confidence: 61%
“…Most of the chromatographic methods are based on gas chromatography/mass spectrometry coupling (GC/MS), requiring the derivatization of polar groups (aminopropanol chain) of compounds [11,14,[17][18][19][21][22][23]25,26]. However, the GC-MS analysis of the most polar ␤-blockers appeared a real analytical, which has limited the use of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been used to determine ␤-blockers in urine, including methods based on spectrofluorimetry [6][7][8], ELISA [9,10], and chromatography [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Most of the chromatographic methods are based on gas chromatography/mass spectrometry coupling (GC/MS), requiring the derivatization of polar groups (aminopropanol chain) of compounds [11,14,[17][18][19][21][22][23]25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of metoprolol and its metabolites by capillary GC-mass spectrometry (GC/MS) as oxazolidinonetrimethylsilyl [11] perfluoroacyl [12] and mixed TFA-TMS [13] has been described. Metoprolol and its metabolites have also been analysed by high performance liquid chromatog- raphy (HPLC) with fluorescence detection [14,15].…”
Section: Introductionmentioning
confidence: 99%